The Challenge of Violence: Toward a Theology of Women's Bodies - Dalton, Anne Marie (Toronto journal of theology, 2000)
This article deals with the bodies of women and with gender. While some of my comments also apply to men's bodies (especially those from oppressed groups), and to violence in general, my assumption is that all bodies are gendered and that certain kinds of violence are also gendered. The violence implied in some of the snapshot accounts above is of this kind: gendered violence. It is enculturated and systemic violence directed against women simply because they are female bodies. Since others have enumerated the horrors of this kind of violence, it is not necessary to do so any further here.4 What I am concerned with is the role of the Christian tradition, not only in the past but also more importantly in the future, in addressing violence against the body, particularly female bodies. How we read the past has a lot to do with what we will create in the future. My contention is that both a more nuanced understanding of what constitutes "the body" and a more careful reading of some aspects of the Christian tradition can produce a foundation for a reconstructed theology of the body. It could be argued that since women were especially associated with the body in the body / soul dualism throughout the Christian West, the recovery of a theology of women's bodies is the critical starting point for any theology of the body.